1994
DOI: 10.1007/bf00374309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thapsigargin and cyclopiazonic acid on the sarcoplasmic reticulum Ca2+ pump of skinned fibres from frog skeletal muscle

Abstract: Thapsigargin has been reported to inhibit ATP-dependent Ca2+ uptake by isolated sarcoplasmic reticulum (SR) vesicles of vertebrate skeletal muscle fibres at nanomolar concentrations. There have been no reports confirming this effect in skinned muscle fibre preparations. We have examined the ability of thapsigargin to inhibit the uptake of Ca2+ by the SR in mechanically skinned fibres of frog iliofibularis muscles, using the size of the caffeine-induced contracture to assess the Ca2+ content of the SR. The SR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
5
33
1
Order By: Relevance
“…Thapsigargin is considered to be highly selective for SERCA, subject to use at low nanomolar concentrations [16]. However, many reports of poor sensitivity to thapsigargin appear in the literature and several contributing factors have been recognized including non-specific adsorption to bulk tissue and plastic surfaces, and indirect competition by calcium [36,37,41,42]. Our finding that the large amount of membranes assayed contributed to the low efficacy of thapsigargin was supported by recent investigations (I. K. Franklin and M. J. Hubbard, unpublished work) of permeabilized enamel cells, where thapsigargin was effective at 20-fold lower concentrations than in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thapsigargin is considered to be highly selective for SERCA, subject to use at low nanomolar concentrations [16]. However, many reports of poor sensitivity to thapsigargin appear in the literature and several contributing factors have been recognized including non-specific adsorption to bulk tissue and plastic surfaces, and indirect competition by calcium [36,37,41,42]. Our finding that the large amount of membranes assayed contributed to the low efficacy of thapsigargin was supported by recent investigations (I. K. Franklin and M. J. Hubbard, unpublished work) of permeabilized enamel cells, where thapsigargin was effective at 20-fold lower concentrations than in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As such a reversal is currently explained by abolition of trans-sarcolemmal Ca2" buffering by the SR, it is likely that a fraction of pumps unblocked by 30 uM TBQ is still able to buffer incoming Ca2". Unfortunately, solubility problems and possible non-specific effects related to membrane partition of hydrophobic compounds (Baudet et al, 1993;Du et al, 1994) precludes complete SR Ca2" pump inhibition and investigation of the reversal phenomenon in multicellular preparations.…”
Section: Specificity Of Tbqmentioning
confidence: 99%
“…In multicellular preparations, the effects of these putative Ca21 pump inhibitors have yielded more disappointing results as concentrations of TG or CPA at least 10 times higher (>50 MM) than in isolated cells have to be used to record significant, and sometimes modest, changes in inotropism and variable effects on SR Ca2+ content (Baudet et al, 1993;Pery-Man et al, 1993;Yard et al, 1994). The use of high concentrations of hydrophobic molecules could provoke membrane partitioning, non-specific binding and possible non-selective effects (Baudet et al, 1993;Du et al, 1994;Yard et al, 1994). Regarding the staircase phenomenon, Yard et al (1994) have reported that application of 30 gM CPA attenuated the positive force-frequency relationship of the guinea-pig atrium, but these data may not be extrapolated to the ventricle, nor did this study investigate the Ca21 load of the SR. Our own experience with TG and CPA in rabbit ventricle (Baudet et al, 1993) (Bers, 1991 for rabbits or with ether followed by exsanguination for rats.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies support our choice of 10 µmol/L CPA, which inhibits SR Ca 2+ uptake in skeletal muscle by approximately 70% in frog skinned fibers 4 and by as much as 100% in rat skinned fibers. 14 Higher concentrations have additional effects, such as increasing the Ca 2+ sensitivity and decreasing peak tension of skinned ferret slow twitch fibers, 12 and increasing the Ca 2+ sensitivity of the contractile apparatus of skinned rat fast twitch fibers.…”
Section: Methodsmentioning
confidence: 84%